(untitled) (Journal of the College of Languages (JCL), 2019)
زمانةوانة بونيادطةرة ئةمريكييةكان لة نيَوانى سالاَنى ( 1925 – 1945 ) بةتيَثةرِبووكات تيؤرى ( فؤنيم)يان ضةسثاند ،بةم جؤرة زمانةوانةكان ئاراستةى كاريان بةرةو مؤرفؤلؤذى طؤرِى بؤية ماوةى نيَوان سالاَنى ( 1940 –1960 ) ليَكؤلَينةوةى مؤرفؤلؤذى بووة خالَى بنةرِةتى (1 ) . جيَى ئاماذةية كة ئةو كةم و كورتيانةى كة لة ثيَناسةى وشةدا دةركةوت هؤكاريَكى سةرةكى بوون بؤ ئةوةى بةدواى جيَطرةوةيةك بطةرِيَن ، كة ئةويش ضةمكى مؤرفيم بوو . ضونكة ريزمانى تةقليدى نةيتوانيبوو بةتةواوى بضيتة بنج و بناوانى وشة و بةسةر يةكةى بضوكترى دابةش بكات ، هةروةها وشةى كردبوو بة بناخة بؤ شرؤظةكردنى زمان . لةطةلَ ئةوةشدا نةيتوانيبوو ثيَناسةيةكى طشتطير بؤ وشة بكات بؤ ئةوةى تيؤريَكى طشتى لةسةر دابمةزريَت و بكريَت بة ضوارضيَوةيةك بؤ شرؤظةكردنى زمان .( 2) This study deals with the subject of the word formation in the Kurdish language depending on the morphological theory, and it relies on words which consisting of number and complex words, which has been called (ذمارةوشة و تيَكضرِذاوةوشة ). It is worth mentioning here that the number has a prominent role in the formation and building Kurdish utterances morphologically, and it has also seen the type of words in the Kurdish language is complex in its formation due to the fall of some of the sounds from the original word and its mixing with another word, which causes a change in the form of the word and it consists complex compound words. Therefore, it has believed that it is necessary to study it in detail. The number of complex and compound words has a great and effective role in building Kurdish utterances. The study found a number of results, perhaps the most prominent one is showing the number of complex words and their prominent role in the Kurdish utterances formation.